IMPLEMENTATION OF THE DEMONSTRATION METHOD TO IMPROVE THE ABILITY OF TEACHERS IN UTILIZING THE ENVIRONMENT AS A LEARNING RESOURCE IN SANTO TARCISIUS DUMAI KINDERGARTEN - Aida Aida (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This research is motivated by the low ability of teachers to use the environment as a source of learning in TK Santo Tarcisius Dumai. This can be seen from the symptoms that there are still many kindergarten teachers who have not implemented the concept of environmentally sound implementation, there are still a few kindergarten teachers who empower the environment as a source of learning, there are still some educational institutions, especially kindergartens, who do not understand the concept of an environmentally sound school. The subjects in this study were teachers who teach in kindergarten. This type of research is school action research (PTS) which aims to determine the success of increasing teachers' abilities in utilizing the environment as a source of learning in teaching through demonstration methods at Kindergarten of Santo Tarcisius Dumai. Based on the results of the analysis and discussion of cycle I and cycle II mentioned above, it can be concluded that the application of the demonstration method can improve the teacher's ability to utilize the environment as a learning resource in Kindergarten of Santo Tarcisius Dumai. In the first cycle, the teacher's ability to use the environment as a learning resource obtained a classical value of 67% and increased in cycle II by 85%.